Conservation of almond germplasm by cryopreservation - Channuntapipat C.; Collins G.; Sedgley M. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Shoot tips of two almond scion cultivars, 'Ne Plus Ultra' and 'Nonpareil 15-1', and an almond-peach hybrid rootstock were successfully cryopreserved using a one-step vitrification technique. Shoot tips, 2-2.5 mm long, were excised, cold-hardened, precultured, and dehydrated in a vitrification solution adopted from Sakai et al. (1990). They were then stored under liquid nitrogen (LN) for up to 6 months. After thawing and culturing the shoot tips, shoot regeneration was usually observed within 2-3 weeks. Shoot survival was 77, 52, and 78 per cent for 'Ne Plus Ultra', 'Nonpareil 15-1' and the hybrid rootstock respectively. All shoots had the same morphological appearance as the initial in vitro cultures. However, the possibility of genetic change during long-term preservation is being investigated.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)